2019
DOI: 10.1016/j.abrep.2019.100168
|View full text |Cite|
|
Sign up to set email alerts
|

A structural MRI study of differential neuromorphometric characteristics of binge and heavy drinking

Abstract: Background Alcohol misuse often manifests in two different patterns of drinking; Binge Drinking (BD; ≥4 (women) or ≥ 5 (men) drinks/day, ≤12 days/month) or Heavy Drinking (HD; ≥3 (women) or ≥4 (men) drinks/day, ≥16 days/month). Although direct comparisons have not been made, structural MRI studies indicate that the two types of drinking behaviors might be associated with different neuromorphometric characteristics. Methods This study used a cross-sectional design to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…As was done in Maksimovskiy et al (2019) and Fortier et al (2020), we defined a binge drinker as an individual who reported a pattern of consuming four or more drinks per day (females) or five or more drinks per day (males) using the lifetime drinking history (LDH) questionnaire (Skinner & Sheu, 1982). Early‐onset adolescent binge drinkers (EBD) consisted of individuals who reported any binge drinking on the LDH prior to age 15 ( n = 50; EBD = 1 + BD day <15 years of age).…”
Section: Methodsmentioning
confidence: 99%
“…As was done in Maksimovskiy et al (2019) and Fortier et al (2020), we defined a binge drinker as an individual who reported a pattern of consuming four or more drinks per day (females) or five or more drinks per day (males) using the lifetime drinking history (LDH) questionnaire (Skinner & Sheu, 1982). Early‐onset adolescent binge drinkers (EBD) consisted of individuals who reported any binge drinking on the LDH prior to age 15 ( n = 50; EBD = 1 + BD day <15 years of age).…”
Section: Methodsmentioning
confidence: 99%
“…In humans, the VP is part of the limbic pallidum, which also includes the globus pallidus. Reduced globus pallidus volumes have been detected in heroin‐dependent individuals (Muller et al, 2019) and in binge drinkers (Maksimovskiy, Fortier, Milberg, & McGlinchey, 2019). Moreover, in one case study, infarcts of the globus pallidus after methadone overdose led to abstinence from opiates and alcohol use for 10 years (Moussawi, Kalivas, & Lee, 2016).…”
Section: Ventral Pallidum (Vp) and Relapsementioning
confidence: 99%
“…In patients with alcohol use disorders (AUD) without cognitive deficits, findings are more inconsistent. Most studies have found atrophy in the prefrontal cortex (PFC) [ 5 , 13 , 23 , 28 , 37 ], but other brain regions have been implicated [ 18 , 24 , 25 , 43 ]. Moreover, diffusion tensor imaging (DTI) studies have shown reduced white matter integrity in several brain regions among patients with AUD [ 43 ].…”
Section: Introductionmentioning
confidence: 99%